1866 Ky. Acts 52, An Act to Prevent Shooting on the Sabbath in this Commonwealth, ch. 656 § 1. - (:unkn) unknown (General Publisher, 1866)
hat No person shall, within this Commonwealth, on the Sabbath day, enter or go upon the land of another person to catch, shoot, or kill any birds, fowl, or animal of any kind; and any such person having in his possession a gun at the time, or after he enters upon the premises of another as aforesaid, shall, upon proof, be guilty of a violation of this act, and, upon conviction thereof, by proceedings before any justice of the peace, in any county of the State . . .
--
Keywords: HUNTING REGULATION